Oxidative dissolution of nickel matte in dilute sulfuric acid solutions - AKTAŞ, SERDAR (ELSEVIER, 2019)
Nickel matte (Ni3S2) is the most common feedstock for producing nickel oxide and nickel metal in associated refineries. Nickel matte is produced from sulfide or laterite ores, and contains around 73 wt% nickel. This study investigated the dissolution parameters of nickel matte in dilute sulfuric acid media in the presence of air as oxidant with the goal of presenting a cost-effective process for leaching nickel matte. The dissolution experiments were carried out to examine the following effects: air flow rate, stirring speed, S/L ratio, acid concentration, reaction temperature, reaction time and the amount of ferrous sulfate added. Nickel extraction of 90% and cobalt extraction of 80% were achieved using dilute H2SO4 and sparging of air as a source of oxygen. To increase the dissolution percentage of the matte, ferrous sulfate addition was studied and the oxidation and reduction potential (ORP) was measured to investigate the effect of ferrous ions on nickel and cobalt recovery. The highest nickel dissolution percentage (95%) was observed with the initial addition of 1200 mg/L Fe (II). Characterization of samples has been carried out with quantitative X-ray diffraction (XRD) and scanning electron microscopy, along with an energy dispersive system (SEM-EDS).
Keywords: Nickel matte; Dissolution; Leaching; Precipitation; Salting out; OXYGEN; SOLUBILITY; KINETICS; NI3S2; CHEMISTRY; BEHAVIOR; COPPER; COBALT; ORES